Soybean meal+sorghum grain, alfalfa hay, and dehydrated alfalfa pellets as protein supplements for beef cows grazing dormant, tallgrass-prairie - T. DelCurto; R.C. Cochran; L.R. Corah; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1989)
Eighty-six pregnant. Hereford x Angus cows were randomly assigned to one of three winter supplement treatments: 1) soybean meal+sorghum grain, 2) alfalfa hay, or 3) dehydrated alfalfa pellets. Cows supplemented with dehydrated alfalfa pellets gained more (P.10) were detected in cow body condition change. reproductive efficiency, or calf growth.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Soybean meal; Sorghum grain; Alfalfa hay; Dehydrated alfalfa pellets; Protein; Dormant; tallgrass-prairie